High‐Purity Hydrogen Production with the Reformer Steam Iron Cycle. Issue 3 (2nd March 2018) - Nestl, Stephan; Voitic, Gernot; Zacharias, Robert; Bock, Sebastian; Hacker, Viktor
Abstract: The decentralized production of renewable hydrogen enables the build‐up of an infrastructure for low‐emissions fuel‐cell‐based power production and mobility. The reformer steam iron cycle (RESC) is introduced as one technological option to realize on‐site hydrogen production by combining production, purification, and storage with a low environmental impact. A hydrogen production prototype is developed, constructed, and operated with mixtures of methane and carbon dioxide as a reference for biogas. Hydrogen with a purity of 99.8 % is produced without the need for an additional gas purification step. Methane and carbon dioxide are identified as the primary impurities in the hydrogen fuel; the carbon monoxide content of the hydrogen produced is in the range of 15–24 ppm in the demonstration phase of the prototype reactor. Abstract : Sustainable hydrogen on demand : The reformer steam iron cycle (RESC) offers the possibility for sustainable decentralized hydrogen production from hydrocarbons such as biogas and methane. The presented small‐scale proof of concept system is capable of producing high‐purity hydrogen.